THE INFLUENCE OF SALINITY AND UREA FERTILIZER DOSAGE ON POPULATION GROWTH OF Spirulina sp. - Sri Ariyati; Tri Retnaningsih Soeprobowati; Hendarko Sugondo (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Research on Spirulina sp. has been development since it was found to have a high economic value and as healthful as human traditional food such as the fishes. Therefore, the factors that influence the culturing of this algae should be maintained properly to obtain a high quality of the product. The research was done to determine the interaction of salinity and the dosage of the urea fertilizer on the population growth of Spirulina sp. factorial design with the combination treatment of four salinities (12,5 ppt, 15 ppt, 17,5 ppt, 20 ppt) and three dosage of urea fertilizer (80 ppm, 100 ppm, 120 ppm), are applied with 3 replications. The result indicated that the highest Spirulina sp. population is 321000 unit/ml, wet weight is 3,349 gr/l and dry weight is 1,315 gr/l which was found on the 20 ppt salinity and 120 ppm of urea fertilizer dosage.